The Effectiveness Of Sand Filters With Variations In Thickness And Sand Diameter In Reducing The Coliform Content Of Dug Well Water - Rokot, Agus; jusran, Mokoginta; Jasman, Jasman; Candhy, Mamarasi (Indonesian Health Journal, 2023)
Water filters are one of the efforts that can be made to reduce the content of contaminants and bacteria in water that do not meet the requirements. Sand and gravel are media that are widely used in filters, which can reduce coliform content levels. This research aims to see the effectiveness of sand filters with variations in the thickness and diameter of sand in reducing the coliform content of dug well water. This type of research is experimental, using pre-test and post-test methods. The population is a sample of dug well water containing Coliform bacteria in Wenang District, Telling Bawah Village. The sample is water that has passed the filtering process 12 times. The instruments in this research were sand filters with variations in diameter and thickness and biological examination of water samples. The research data was then tested using the t-test. The research showed that sand filters with a thickness of 70 cm and a diameter of 0.45 mm were ineffective in reducing coliform content. In comparison, sand filters with a thickness of 70 cm with a diameter of 0.3 mm and sand filters with a thickness of 90 cm with a diameter of 0.45 mm and a diameter of 0.3 mm effectively reduce the Coliform content in dug well water. The results of statistical tests using the t-test on a 70 cm thick sand filter with a diameter of 0.45 mm showed a value of 0.219 (p > 0.05). A sand filter with a thickness of 70 cm with a diameter of 0.3 mm shows an ap value of 0.001 (p < 0.05). A 90 cm thick sand filter with a diameter of 0.45 mm showed a value of 0.001 (p < 0.05). A 90 cm thick sand filter with a diameter of 0.3 mm shows an AP value of 0.000 (p < 0.05).